Sharing teacher knowledge at scale: teacher inquiry, learning design and the representation of teachers' practice. Issue 4 (8th August 2018) - Oliver, Martin; Avramides, Katerina; Clark, Wilma; Hunter, Jade; Luckin, Rose; Hansen, Cecilie; Wasson, Barbara
Abstract: Sharing teachers' professional knowledge remains challenging. Teachers' development often remains ad hoc or local, and attempts to scale this up have proved problematic. To address this, research in areas such as 'learning design' has explored the use of formal representations of practice. This proposes that educational practice can be improved by documenting, sharing and building on what teachers already do. Whilst this has led to some successes, it has not resulted in the widespread transformation of practice. This paper reviews the literature about sharing teacher knowledge. The challenges of scaling up development are then considered in relation to two theories that help explain the challenges: Communities of Practice and Sociomateriality. This analysis is illustrated through case studies in Norway and the UK. These show that teachers already create and share artefacts that represent their pedagogic knowledge. However, they found formal representations, such as learning designs, difficult to work with. The paper concludes that scaling up teacher development using abstract formalisms is unlikely to succeed. Instead, teachers value stories and the materials they already create in their day-to-day practice. It is this intermediate level of representation, between direct experience and formal abstraction, that offers the most promise for sharing practice.